External and gastrointestinal parasites of the rufous-collared sparrow Zonotrichia capensis (Passeriformes, Emberizidae) in Chile - Llanos Soto, Sebastián (2017)
A total of 277 rufous-collared sparrows, Zonotrichia capensis Müller, 1776 (Emberizidae), were examined for external parasites. The birds were captured using mist nets in seven locations in northern and central Chile. Additionally, seven carcasses from central Chile (the Biobío region) were necropsied to evaluate the presence of endoparasite infection. Ectoparasites were found on 35.8% (99/277) of the examined birds and they were represented by the following arthropods: feather mites Amerodectes zonotrichiae Mironov and González-Acuña, 2014 (Analgoidea: Proctophyllodidae), Proctophyllodes polyxenus Atyeo and Braasch, 1966 (Analgoidea: Proctophyllodidae), and Trouessartia capensis Berla, 1959 (Analgoidea: Trouessartiidae); a louse Philopterus sp. (Phthiraptera: Ischnocera); and ticks Amblyomma tigrinum Koch, 1844 (Acari: Ixodidae) and Ixodes auritulus Neumann, 1904 (Acari: Ixodidae). Two of the seven necropsied carcasses were infected with the acanthocephalan Mediorhynchus papillosus Van Cleave, 1916 (Gigantorhynchida: Gigantorhynchidae). To our knowledge, this study reports P. polyxenus, Philopterus sp., A. tigrinum, and M. papillosus for the first time for Z. capensis and expands the distributional range for T. capensis to Chile.